Microplastics in Oreochromis Niloticus: An Abundance Study and Health Risk Assessment Around the Gajah Mungkur Reservoir - Nugroho, Aldy Wahyu; Nurika, Globila; Adi, Dhuha Itsnanisa (Universitas Airlangga, 2025)
Introduction: More than 430 million tons of plastic waste are added globally each year, increasing the potential distribution of microplastics, particularly in aquatic environments. Microplastic contamination in the Gajah Mungkur Reservoir is thought to come from nearby textile factories and fish farming using plastic floating nets. This study differs from previous research that only identified microplastics in reservoir water by conducting an individual-based carcinogenic health risk assessment using primary data. This study aims to identify the characteristics of microplastics in Oreochromis niloticus (abundance of particle, shape, color, and polymer type) and assess the carcinogenic risks of the local community. Methods: This quantitative descriptive research used 9 Oreochromis niloticus samples from floating net cages and 30 respondents selected through purposive sampling techniques. Microplastics were identified using a stereomicroscope and FTIR. The Microplastic Carcinogenic Risk (MPCR) formula was applied. The research ran from November 2024 to March 2025. Results and Discussion: Microplastics in Oreochromis niloticus had an average abundance of 0.45 particles/gram, with the highest at 0.87 particles/gram. The estimated daily intake of microplastic particles in respondents shows an average result of 0.007730 particles/day. The average MPCR value of respondents is 1.86×10-6, indicating a carcinogenic risk level according to US EPA guidelines, although still within tolerable limits. Conclusion: The average respondent is at risk of carcinogenic microplastics but still within tolerance limits. Suggestions for the community are not to throw garbage and household waste into the rivers around the reservoir and to reduce single-use plastics.